Number of natural killer cells and cytokine levels in peripheral blood at various degrees of severity - Devita, Ninda; Arjana, Adika Zhulhi; Intansari, Umi Solekhah; Susilowati, Rina (Communications in Science and Technology, 2023)
This study aims to investigate NK cell number and cytokines level in various degrees of severity in COVID-19 cases. A total of 63 COVID-19 patient aged >18 y were divided into mild-moderate and severe-critical groups. Patient characteristics and peripheral blood count were obtained from medical records. NK cells number, levels of IFN-?, IL-10, and IL-12 in peripheral blood were examined by means of flow cytometry. The severe-critical group had leukocytosis, neutrophilia, lymphopenia, higher Neutrophil Lymphocyte Ratio, lower NK cell number and higher level of IL-10. In severe-critical group, those aged >60 years had higher IL-10. In both groups, patients with diabetes comorbidities had a higher number of NK cells (p<0.05). NK cell number and IL-10 in peripheral blood have potential as a predictor of severe COVID-19 patients.